Writing Skill in Teaching English: An Overview - Annisa Raudatus Sa’adah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
Writing skill is a hard skill among others because it has to be a concern more about it, and we need to follow some rules that related to every single step, they are word choice, coherent, correlation, and grammar. The students should choose the proper word to express meaning so that the readers catch what information they wrote. The information of each paragraph, main idea, and the argumentation of the researcher should be coherent. Grammar also plays important role in writing. The use of correct grammar will not be confusing the readers. Moreover, the error of using grammar will make a serious misunderstanding toward the readers. The successful of learning writing is not merely depending on the students, but it needs a teacher contribution to reach the learning of English writing.